Business Risks of The International Company GREE Electric Appliances Inc. (GREE) In A Pandemic - Fei Zhou; Victoria Chernova (Communications of International Proceedings, 2021)
Fierce competition in the markets of the modern international economy requires a clear definition of the prospects and directions for the development of entrepreneurial activity, taking into account the likelihood of risks of an objective and subjective nature. The dual nature of the nature of risk and the degree of its impact on the development of entrepreneurial activity are independent of the will of a person and are not regulated by it. But it is precisely the presence of two components in the nature of risk that makes it possible to choose more effective methods and techniques for optimizing management decisions and minimizing the risks themselves. By creating the necessary control environment, constantly informing staff and exercising internal control, the economic entity makes appropriate decisions on risk management. The article will consider the risks that threaten the Chinese company GREE, which operates in the international market in a pandemic.
Keywords: Risks; Business Risks; Threats; Pandemic; World Crisis; International Business; External Risks; Internal Risks.